2019
DOI: 10.1111/jan.14174
|View full text |Cite
|
Sign up to set email alerts
|

Asthma control and acute healthcare visits among young adults with asthma—A population‐based study

Abstract: Aims To study asthma control and acute healthcare visits among young adults with asthma. Background Despite the access to effective treatment and nursing interventions, poor asthma control is still common among individuals with asthma. However, studies describing clinical characteristics among young adults with asthma are rare. Design A population‐based cohort study. Methods In 2015, as a part of the OLIN paediatric cohort I (recruited in 1996 at age 7–8 years), N = 2,291 young adults (27–28 years) completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…An European study carried out in 2014 on 8000 adult asthmatics reported a prevalence of uncontrolled asthma of 45%. 16 , 17 In our study, 73% of patients had a good evolution of their asthma during their adult follow-up, with persistent control (ACT ≥20). The continuation of follow-up in an adult centre contributed to the maintenance of well controlled disease and good respiratory function at 3 years after transition.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…An European study carried out in 2014 on 8000 adult asthmatics reported a prevalence of uncontrolled asthma of 45%. 16 , 17 In our study, 73% of patients had a good evolution of their asthma during their adult follow-up, with persistent control (ACT ≥20). The continuation of follow-up in an adult centre contributed to the maintenance of well controlled disease and good respiratory function at 3 years after transition.…”
Section: Discussionsupporting
confidence: 47%
“… 8 This suggests that it would be interesting to continue the follow-up of our cohort beyond 3 years. The persistence of poor asthma control in this subgroup may be explained by different factors: more severe allergic asthma, asthma difficult to control, irregular medical follow-up or poor adherence to treatments, 16 but may also represent a specific subgroup of patients with severe asthma. These observations were also found in patients with uncontrolled asthma in our cohort, where asthma was predominantly allergic; three patients in this subgroup had a break in follow-up for >12 months.…”
Section: Discussionmentioning
confidence: 99%
“…In a Swedish population study of individuals in their late 20s with asthma, it was found that long-standing cough and sputum production were more common in women (Selberg et al 2019). Additionally, in the same cohort, a higher proportion of women were current smokers, and current smokers more frequently had uncontrolled asthma, which is a finding that has previously been shown in Nordic countries.…”
Section: Asthmasupporting
confidence: 53%
“…But from the multicenter, cross-sectional study published before, it was shown that only 28.5% Chinese patients achieved the complete control of asthma (3). The worse control of asthma results from many factors, including age, gender, unhealthy lifestyle, poor family environment, family history, allergies, poor medication compliance and lack of knowledge and selfmanagement of the disease (4)(5)(6)(7). It is necessary to assess the knowledge level and competencies of the patient before initiating patient education in order to carry out personalized asthma education effectively (8,9).…”
Section: Introductionmentioning
confidence: 99%